Neolithic transverse arrowheads: a great misunderstanding - Wadskjær, Andreas Valentin (Danish Journal of Archaeology, 2018)
One of the most debated subjects in archaeology is the transition between the Mesolithic and the Neolithic period. A missing piece in this debate has been the transverse arrowhead, which is a relic from the hunting and gathering society but still has its place in the new agrarian societies. What we think we know about transverse arrowheads from Southern Scandinavia is based on a more than 75 years old theory, which hypothesises that Neolithic arrowheads were manufactured from irregular or polished flakes. This article offers a critical review of research so far into transverse arrowheads in Southern Scandinavia. It does so by proposing a new typo-chronology of Neolithic arrowheads from this region, which demonstrates how the transverse arrowhead developed from the Late Mesolithic to the Middle Neolithic, and it is actually the first study with the main focus on this subject. The study is concluded with a discussion that argues the empirical basis for the typological restructuring and highlights the implications of the study for the broader debate on Neolithisation.